The Relationship between Local Wisdom-Based Diet and Gastritis Incidence in Berau 5 State Vocational School Students in Segah District - Muhd, Aras; Joko Sapto Pramono; Mustaming (Indonesian Journal of Sport Management and Physical Education, 2023)
Gastritis is a social and public health problem in both developed and developing countries, especially in adolescents. They are required to live independently and at this age teenagers often do not eat breakfast or eat too late. So the purpose of this study was to determine the relationship between eating patterns based on local wisdom and the incidence of gastritis in students of SMK Negeri 5 Berau in Segah District. This type of quantitative research with analytic study and cross sectional design. The population is 187 students who are at SMK Negeri 5 Berau in Segah District. Then the data were analyzed univariately and bivariately with the Chi Square test. Diet includes meal times, meal frequency and types of food. There is a relationship between the time and frequency of eating with the incidence of gastritis at SMK Negeri 5 Berau, Segah District. While there is no relationship between the type of food and the incidence of gastritis at SMK Negeri 5 Berau, Segah District